2012
DOI: 10.1158/0008-5472.sabcs12-s4-2
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S4-2: Targeted intraoperative radiotherapy for early breast cancer: TARGIT-A trial- updated analysis of local recurrence and first analysis of survival

Abstract: Background TARGIT-A, an international phase 3 randomised trial (Lancet 2010;376:91–102) compared outcomes in patients undergoing breast conserving surgery followed by either whole breast external beam radiotherapy (EBRT) over several weeks, or a risk-adaptive approach using single dose targeted intra-operative radiotherapy (TARGIT). Risk-adaptive approach meant that if the final pathology report demonstrated unpredicted pre-specified adverse features, then EBRT was to be added to TARGIT. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…They concluded: "The overall recurrence rate of the TARGIT-A trial have remained stable with a longer followup and it is therefore statistically implausible that one particular arm has a signifi cantly higher local recurrence." The latest TARGIT-A updates, presented at the 2012 SABCS [ 50 ] and published in Lancet [ 51 ], showed that the earlier optimism expressed in the 2010 Lancet publication and the 2011 SABCS poster was likely unfounded. An additional 1,219 patients were added to TARGIT-A since the 2010 Lancet publication, for a study total of 3,442 patients.…”
Section: Apbi Clinical Results: Orthovoltage (50 Kv X-rays) Prospectmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded: "The overall recurrence rate of the TARGIT-A trial have remained stable with a longer followup and it is therefore statistically implausible that one particular arm has a signifi cantly higher local recurrence." The latest TARGIT-A updates, presented at the 2012 SABCS [ 50 ] and published in Lancet [ 51 ], showed that the earlier optimism expressed in the 2010 Lancet publication and the 2011 SABCS poster was likely unfounded. An additional 1,219 patients were added to TARGIT-A since the 2010 Lancet publication, for a study total of 3,442 patients.…”
Section: Apbi Clinical Results: Orthovoltage (50 Kv X-rays) Prospectmentioning
confidence: 99%
“…28.12b ) which was presented at the SABCS but not shown in the Lancet publication. The nearly statistically breast recurrences (ipsilateral, regional, contralateral, and distant) [ 50 ]; ( c ) pre-pathology only TARGIT-A ipsilateral recurrences [ 51 ] signifi cant difference in overall breast recurrences in the two groups ( p = 0.053) is a reason for concern, especially since the breast cancer deaths are already, even at 29 months median follow-up, higher with TARGIT (20 deaths, 2.6 %) than with EBRT (16 deaths, 1.9 %),…”
Section: And 287 )mentioning
confidence: 99%
“…Kolejnym badaniem z randomizacją było badanie TAR-GIT A, którego wyniki zostały opublikowane w 2010 r. [36] i uaktualnione na Konferencji w San Antonio w 2012 roku [37]. W grupie 3 451 chorych przydzielanych do losowo napromieniania 1 frakcją 20 Gy promieniami rtg o energii 50 kV lub do ramienia kontrolnego napromienianiem standardowym na całą pierś, po czasie obserwacji 2 lat i 5 miesięcy w ramieniu badanym stwierdzono 3,3% wznów w piersi w porównaniu z 1,3% w ramieniu kontrolnym (p = 0,04).…”
Section: Wyniki Badań Randomizowanychunclassified
“…W grupie 3 451 chorych przydzielanych do losowo napromieniania 1 frakcją 20 Gy promieniami rtg o energii 50 kV lub do ramienia kontrolnego napromienianiem standardowym na całą pierś, po czasie obserwacji 2 lat i 5 miesięcy w ramieniu badanym stwierdzono 3,3% wznów w piersi w porównaniu z 1,3% w ramieniu kontrolnym (p = 0,04). Zaobserwowano też statystycznie większą liczbę wznów lokoregionalnych i przerzutów odległych w ramieniu z APBI (p = 0,02) [37].…”
Section: Wyniki Badań Randomizowanychunclassified
“…While initial data with short follow-up (median follow-up \2 years) and limited events (n = 11) was promising, a recent update found that IORT, even with WBI supplementation in one-fifth of the IORT cohort, was associated with inferior local control at 5 years (3.3 vs. 1.3 %, p = 0.04). 7,8 A second randomized trial from Milan randomized 1,186 patients to IORT or WBI. This trial used IORT delivered with electrons (21 Gy delivered to the 90 % isodose line).…”
mentioning
confidence: 99%